Medical Imaging and Image-Guided Interventions - Sebro, Ronnie A. (IntechOpen, 2019)
"Medical Imaging and Image-Guided Interventions" is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in this field of study. This publication aims at providing a thorough overview of the latest research efforts and opens new possible research paths for further novel developments.